2018
DOI: 10.1148/radiol.2017171260
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of CT Features for Differentiating Complicated and Uncomplicated Appendicitis

Abstract: Purpose To perform a systematic review and meta-analysis to identify computed tomographic (CT) features for differentiating complicated appendicitis in patients suspected of having appendicitis and to summarize their diagnostic accuracy. Materials and Methods Studies on diagnostic accuracy of CT features for differentiating complicated appendicitis (perforated or gangrenous appendicitis) in patients suspected of having appendicitis were searched in Ovid-MEDLINE, EMBASE, and the Cochrane Library. Overlapping de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 49 publications
5
99
0
Order By: Relevance
“…Differential diagnosis between these two forms acute appendicitis without imaging is not feasible [35]. There is a need for determining CT criteria that could help reliably identify complicated acute appendicitis [4] and also incidental appendiceal neoplasms to ensure their surgical resection [36]. Several CT features suggestive of coexisting appendiceal tumor have been described, but frequently, the radiographic appearance is one of acute appendicitis [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential diagnosis between these two forms acute appendicitis without imaging is not feasible [35]. There is a need for determining CT criteria that could help reliably identify complicated acute appendicitis [4] and also incidental appendiceal neoplasms to ensure their surgical resection [36]. Several CT features suggestive of coexisting appendiceal tumor have been described, but frequently, the radiographic appearance is one of acute appendicitis [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In order to optimize and tailor the treatment for acute appendicitis, precise and accurate diagnostic tools, such as computed tomography (CT) are required. As CT has high sensitivity in diagnosing acute appendicitis, it has become the golden standard in right lower quadrant abdominal pain differential diagnosis [4]. Uncomplicated acute appendicitis may also resolve spontaneously without even antibiotics, let alone surgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, there is excellent inter-observer agreement of peri-appendicular fat stranding, uid collection and focal cecal thickening. Phlegmon was de ned as diffuse and substantial in ammation of the periappendiceal fat with ill-de ned but not rim-enhancing uid collections and abscess is de ned as a discrete collection with rim enhancement (15)(16)(17). Another study added that peri-appendiceal uid collection revealed area under the curve of 0.80, sensitivity of 77%, and accuracy of 80% and the highest speci city (100%) is recorded for the presence of extraluminal air and a perityphlitic abscess (27).…”
Section: Discussionmentioning
confidence: 99%
“…Another study added that peri-appendiceal uid collection revealed area under the curve of 0.80, sensitivity of 77%, and accuracy of 80% and the highest speci city (100%) is recorded for the presence of extraluminal air and a perityphlitic abscess (27). Another study added that the peri-appendiceal fat stranding is the only feature with high sensitivity (94%) for diagnosis of acute appendicitis (17). Previous studies reported that presence of gas in the surrounding peri-appendicular tissue is sign of acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation